Schools and diversity - Keefee, Mary.; Carrington, Suzzane (Australia : Pearson Education Australia, 2007)
Schools and Diversity' is designed to provoke critical thinking about school policies, processes and practices, especially from the viewpoint of those students and parents who have been previously excluded or alienated from quality educational experiences. The text deliberately challenges the narrow focus of more traditional approaches to educational achievements by preparing teachers to maximise learning outcomes for all students. By developing a critical and intellectual teaching role for teachers, the text encourages school communities to support teachers to question, challenge and move outside the traditional assumptions and practices associated with education. In doing so, the text proposes that collaborative processes are integral to maintaining a relevant and connected school community of learners and that effective communication processes can create social capital in schools that promote learning. By contextualising the revolutionary changes in education in clear theoretical terms, the text provides a framework of pedagogical practices that improves learning for a diverse range of students along with curriculum suggestions for teaching and learning.
Includes index.
Keywords: Educational equalization -- Australia; Inclusive education -- Australia; Educational equalization